The Effect of Cucumber (Cucumis sativus) Extract Cream on VEGF and IL-10 in Xerotic Rats - Yanti, Erica Lidya; Harlisa, Pasid; Zulaikhah, Siti Thomas (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Xerosis cutis is a chronic dry skin condition aggravated by impaired skin barrier function and increased transepidermal water loss (TEWL). Decreased levels of interleukin-10 (IL-10) and vascular endothelial growth factor (VEGF) contribute to prolonged inflammation and hinder tissue regeneration. Cucumber (Cucumis sativus) contains flavonoids and vitamin C, which possess anti-inflammatory and angiogenic properties, making it a promising candidate for natural topical therapy. This study aimed to determine the effect of cucumber extract cream on IL-10 and VEGF levels in the skin of female Wistar rats with grade II xerosis cutis induced by acetone and ethanol. This experimental research employed a post-test only control group design. A total of 30 Wistar rats were randomly divided into five groups: normal control, negative control, positive control (10% ceramide cream), and two treatment groups receiving cucumber extract cream at concentrations of 3% and 5%. Following the induction of xerosis, the respective creams were applied topically for 14 consecutive days. Results showed that administration of 5% cucumber extract cream significantly increased VEGF levels (715.75 ± 152.65 ng/L) and IL-10 levels (200.35 ± 43.49 pg/mL) compared to the negative control (VEGF 494.29 ± 95.05 ng/L; IL-10 120.62 ± 22.11 pg/mL, p<0.05). The 3% cucumber extract cream also elevated VEGF (522.96 ± 115.48 ng/L) and IL-10 (197.86 ± 31.32 pg/mL), though less effectively than the 5% formulation. Meanwhile, the group treated with ceramide 10% cream showed increases in VEGF (694.87 ± 180.52 ng/L) and IL-10 (140.85 ± 32.42 pg/mL), indicating that cucumber extract at 5% comparable to ceramide therapy. In conclusion, cucumber extract cream, particularly at 5% concentration, significantly enhances IL-10 and VEGF levels in the skin of xerosis cutis model rats. These findings indicate its potential as an effective natural topical therapy for reducing inflammation and promoting skin regeneration in xerosis cutis caused by chemical exposure.